Self-assembled alkanethiol monolayers on gold surfaces: resolving the complex structure at the interface by STM - Guo, Quanmin; Li, Fangsen (Physical chemistry chemical physics : PCCP, 2014)
The surface properties of metals and metal oxides can be modified by adding a single layer of organic molecules. A most popular route for depositing such a molecular layer is via the formation of self-assembled monolayers (SAMs). The molecules that form SAMs have a functionality which binds to the surface and the adsorption is self-regulated to terminate at exactly one single molecular layer. The very first example, which has become the most widely studied system, of SAMs on metal surfaces consists of chemisorbed alkylthiolate on gold. Despite the simplicity in the preparation of alkanethiol SAMs and the seemingly straightforward structure of such SAMs, the detailed bonding between the sulfur head group and gold is still subject to debate. Experimental and theoretical effort in the last six years has led to a much improved understanding of this classical system of SAMs. In this review, we will highlight the most recent progress in the study of the interfacial structure of alkanethiol SAMs on gold. We focus on the important phenomenon of phase transition that occurs from n -propanethiol to n -butanethiol, and propose a unified structural model to explain how the (3 × 4) phase for short chain alkanethiol monolayers (methyl-, ethyl- and propylthiolate monolayers) changes into the (3 × 2√3)-rect./ c (4 × 2) phase for long chain molecular monolayers. New insights into the classical system of self-assembled alkanethiol monolayers on Au(111).